The quality effects of agency staffing in residential aged care. (23rd August 2022) - Ma, Nelson; Sutton, Nicole; Yang, Jin Sug; Rawlings‐Way, Olivia; Brown, David; McAllister, Gillian; Parker, Deborah; Lewis, Rachael
Abstract: Objectives: In Australia, temporary agency workers are a relatively small but enduring component of the residential aged care workforce. However, evidence from other countries suggests reliance on agency workers has a detrimental effect on the quality of care (QoC). We examined whether QoC outcomes differ for Australian residential aged care facilities (RACFs) based on their reliance on agency care staff. Methods: A retrospective observational study was conducted using de‐identified datasets obtained under the legal authority of the Royal Commission into Aged Care Quality and Safety. Regression analysis was conducted using data comprising 6221 RACF‐year observations, across 5 years (2015–2019), from 1709 unique RACFs in Australia. Results: After controlling for other determinants of QoC, RACFs with a greater reliance on agency care staff have poorer QoC outcomes, with significantly higher rates of complaints, missing persons, reportable assaults, hospitalisations, and accreditation flags. Conclusions: Consistent with international evidence, we found that the QoC of Australian RACFs is sensitive to the reliance on agency staff in delivering direct care to residents. These findings illustrate the importance of workers' employment conditions, alongside other workforce characteristics, in driving the quality of residential aged care.